2022
DOI: 10.1111/cen.14794
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping primary aldosteronism by inconclusive adrenal vein sampling: A derivation and validation study in a tertiary centre

Abstract: Objective: Indices based on aldosterone/cortisol (A/C) concentration in the successfully cannulated adrenal vein (AV) and in the inferior vena cava (IVC) (AV/ IVC) appear to be possible markers to verify the subtype of primary aldosteronism (PA) in the case of inconclusive results of adrenal vein sampling (AVS). The variability of results in previous studies encouraged us to calculate AV/IVC and adrenal A/C cutoff values that could predict the aetiology of PA. Methods: This retrospective study included 96 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Of greater significance, among the patients with "inconclusive" AVS and only unilateral cannulation success, 3 out of 4 achieved AC > 3.5 or AV/IVC > 3.4 for the affected gland and the one patient with left-sided suppressed AV/IVC did not achieve the suppression index of A/C ≤ 0.63 or AV/IVC ≤ 0.37. Therefore, the cutoffs proposed by Tomsic et al 1 appear conservative in our opinion and would have consigned two out of our five patients with "inconclusive" AVS to long-term medical therapy rather than curative surgery. Notably, we report a biochemical remission rate of 100% and a clinical remission rate of 80% in our small cohort of patients with successful and "inconclusive" AVS.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Of greater significance, among the patients with "inconclusive" AVS and only unilateral cannulation success, 3 out of 4 achieved AC > 3.5 or AV/IVC > 3.4 for the affected gland and the one patient with left-sided suppressed AV/IVC did not achieve the suppression index of A/C ≤ 0.63 or AV/IVC ≤ 0.37. Therefore, the cutoffs proposed by Tomsic et al 1 appear conservative in our opinion and would have consigned two out of our five patients with "inconclusive" AVS to long-term medical therapy rather than curative surgery. Notably, we report a biochemical remission rate of 100% and a clinical remission rate of 80% in our small cohort of patients with successful and "inconclusive" AVS.…”
mentioning
confidence: 66%
“…To the Editor, We read the article by Tomsic et al 1 on the role of subtyping primary hyperaldosteronism (PA) with inconclusive adrenal vein sampling (AVS), with great interest. Although AVS remains the gold standard procedure for subtyping PA, successful bilateral cannulation remains a challenge for centres with low procedure volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AVS is required in bilateral PA (including the ACS subgroup), and aldosterone as well as cortisol should be assessed; the procedure is not automatically available in many centres, and sometimes the results are inconclusive or display a high variability in PA, despite an experienced team [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. However, AVS brings supplementary information to imaging procedures allowing better surgical decisions, with a success rate of 76–90%, and the presence of concomitant cortisol excess is mandatory for assessment [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 104 , 105 ].…”
Section: Approach Of Connshing Syndromementioning
confidence: 99%
“…Several studies have suggested that, in the event of failed cannulation of one adrenal veins, the unilateral index, namely the aldosterone-cortisol ratio of the adrenal vein divided by the same ratio in the inferior vena cava (IVC), can distinguish between unilateral and bilateral primary aldosteronism [23][24][25][26][27][28][29][30][31][32]. Most studies have reported the unilateral AV/IVC index using ACTH-stimulated AVS [24][25][26][27][28][29][30]32]. One study reported the index based on non-ACTH stimulated AVS [23], which is common practice in many centres.…”
Section: Introductionmentioning
confidence: 99%